ISSUES OF INCREASING THE OPERATIONAL RELIABILITY OF EXISTING BUILDINGS AND STRUCTURES - Mirzaakhmedova U.A. (Journals Park Publishing, 2022)
In the article, very important problems are the quality of existing buildings and structures, their reliability, durability, durability, durability. Information is provided on measures to eliminate damage and raids caused by deformations in buildings and structures in operation, to improve the reliability of buildings.
Keywords: reliability of buildings, durability, operation process, service life, economic efficiency, maintenance of buildings in good condition.